A Content Analysis of Published Articles in Montenegrin Journal of Sports Science and Medicine from 2012 to 2017 - Miomir Maros (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2017)
Montenegrin Journal of Sports Science and Medicine (MJSSM) is a scientific journal that exists for five years and has so far released 65 scientific papers in 11 editions. The papers are from various fields of sports science - biomechanics, physiology, sports medicine, anthropology, methodology and other areas of sports. In this paper, we classified works by fields, method of address analysis and found that the most numerous works from the physiology of sports, which are the most cited and best quoted in scientific databases. We have also established that the published works had themes - the most up-to-date tendencies in sports science. These research can be useful for further theoretical research, as well as for theoreticians. The authors of the works are researchers from all over the world, as well as the editorial board. The MJSSM includes works from exact disciplines, primarily physiology of sports, as well as from social sciences, thus achieving a synergistic effect. The highly cited topics in the field of physiology of sports are raised by the work of social sciences. These topics when they find themselves in the magazine with a social label increase their own visibility.